Dietary calcium and non-phytate phosphorus levels affect performance, follicular development, and egg quality of native chicken at peak laying period - L.F. Cheng; Q.Q. Zhang; W.Y. Zhao; C. Chang; X. Wang; Z.X. Yan; J. Cao; H.G. Liu; A.L. Geng (Poultry Science)
The experiment aimed to study effects of dietary calcium (Ca) and non-phytate phosphorus (NPP) levels on performance, follicular development, egg quality and serum biochemical indices in native bird-Beijing You Chicken (BYC). A 3 × 3 factorial design was adopted, dietary Ca levels were 2.8 %, 3.2 % and 3.6 %, dietary NPP levels were 0.33 %, 0.38 % and 0.43 %. A total of 972, 28-wk-old BYC laying hens were randomly divided into 9 groups with 4 replicates per group, and 27 birds per replicate. The trial was conducted after 2 wks of pre-adaptation. The performance was determined during 30∼35 wks, 36∼41 wks and 30∼41 wks; follicular development, egg quality and serum biochemical indices were determined at 41 wks of age. The results showed that dietary Ca and NPP levels alone and the interaction affected feed egg ratio (FER) of BYC during 30∼35 wks (P < 0.05), the FER was the lowest (2.65±0.05) and the egg-laying rate was the highest (77.45±3.19 %) in the group with 3.6 % Ca and 0.43 % NPP. Dietary 0.33 % NPP and 0.43 % NPP increased the number of small yolk follicles (P < 0.05). Dietary 3.6 % Ca deepened the yolk color (YC) (P < 0.001), dietary NPP level affected the YC, Haugh unit (HU), relative yolk weight (RYW) and relative albumen weight (RAW) (P < 0.05). The interaction of dietary Ca and NPP levels affected eggshell color (ESC) (P < 0.05), YC (P < 0.001), and relative eggshell weight (RESW) (P < 0.001), also had the trend to affect eggshell strength (ESS) (P = 0.073), albumen height (AH) (P = 0.077) and HU (P = 0.055). 4) 0.43 % NPP had a trend to affect malondialdehyde (MDA) (P = 0.064). In summary, dietary Ca and NPP levels alone and the interaction did not affect egg production of BYC, and FER in the group with 3.6 % Ca and 0.43 % NPP seemed to be the lowest during 35∼41 wks. Dietary NPP may be related to pre-graded follicular development. The recommended dietary Ca level is 3.6 % and NPP level is 0.43 % for BYC during the peak laying period. The Ca/NPP ratio in the range of 8.39∼9.67 may be beneficial to laying performance and egg quality of laying hens.